THE IMPACT OF MANADO LIVE ONLINE HOUSE ON "ER-SHOP OK" SALES PERFORMANCE IN INCREASING SALES VOLUME - Veren Pangemanan; Joy Elly Tulung; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
The purpose of this study was to determine the effect of Rumah Live Online Manado on the sales performance of ER-SHOP OK in increasing sales volume. This study uses a qualitative method. Data were collected through interviews, observation and documentation. There are three data analysis used, namely: (1) data reduction, (2) data presentation, (3) drawing conclusions/verification. Based on the results of the interviews, it can be concluded: 1. The increase in sales was caused by the use of social media Facebook in marketing and providing information about scooping snacks to the public so as to provide opportunities in sales. 2. Business actors "ER-SHOP OK" can sell 30-50 scoops of snacks with how many times live broadcasts a day. 3. It is important to regularly post products on Facebook or live broadcasts as a way to attract customers and provide rewards such as bonuses, money transfers or credits. 4. In snack sales, the â€œER-SHOP OKâ€ store serves purchases within and outside the city with a guarantee that can make customers feel safe and comfortable.